Relationship Between Academic Motivation and Academic Performance of Secondary School Students in Mathematics - Ebele Chinelo Okigbo; Odiri E Onoshakpokaiye (ILIN Institute Makassar, 2023)
The study looked at the relationship between academic motivation and secondary school students’ academic performance in mathematics. A correlation survey was used in the study. The study was guided by two research questions and two hypotheses tested at 0.05 alpha level. A sample of 1,650 students was selected using a multistage sampling procedure from among 42,299 senior secondary two (SS2) students studying mathematics in Delta State, Nigeria, in the academic year 2021-2022. The Academic Motivation Questionnaire (AMQ), validated by three experts was used as the instrument for gathering data and had a reliability value of 0.68 using Cronbach Alpha. The students’ performance in the subject is reflected in their examination scores in mathematics for the SS1 class of 2021-2022. The gathered data were analyzed using Pearson product moment correlation. The results of the study showed a negative connection, and the majority of the students reported strong levels of motivation. Academic motivation and students’ performance in mathematics did not significantly correlate. Students' academic performance in mathematics also differed significantly between those with strong and low motivation. In light of the findings, it was suggested, among other things, that mathematics teachers and guidance counselors in schools should make a concerted effort to increase the motivation of their students through proper teaching and conditioning as well as modeling the behaviour of the students for better performance in mathematics.